Germination of a new economic discipline of cognoeconomics (cognomics) -as a result of the development of cognitive sciences and technologies - Karenov, R.S. (BUKETOV BUSINESS REVIEW, 2018)
It is emphasized that the emerging new economic discipline - cognitive economics (cognomics) is based on the results of studying the functioning of the human brain. It is concluded that medications of the «cognitive direction» occupy and will occupy an important place in the mid-term and long-term perspective in the cogno-economics of the innovative technological civilization of the 21st century. It is noted that the knowledge economy is, on the one hand, the basis of innovative development and at the same time represents a high stage of development of the post-industrial economy, in which knowledge and human capital become the main factors and goal of economic growth. It justifies the role of human capital in the knowledge economy and the direction of its growth, which will accelerate the transition of the domestic economy to a new path of innovative development. Attention is paid to the concept of the cognosphere, which is a sphere of consciousness (cognition, cognitiveness), covering the material part of the activity of the human brain. Is studyig the scheme of the integral balanced system of society and the economy of knowledge, as well as the noosphere, from which the innovative-technological civilization of the XXI century will be formed. It is proved that society and the economy of knowledge, the noosphere, or the sphere of the Mind of man and mankind as a whole should determine the development of innovative technological civilization of the XXI century, new principles of interaction between nature and man.